Cost-effectiveness of Screening for Nasopharyngeal Carcinoma among Asian American Men in the United States. (July 2019) - Harris, Jeremy P.; Saraswathula, Anirudh; Kaplun, Brian; Qian, Yushen; Chan, K. C. Allen; Chan, Anthony T. C.; Le, Quynh-Thu; Owens, Douglas K.; Goldhaber-Fiebert, Jeremy D.; Pollom, Erqi
Objective: Most patients with nasopharyngeal carcinoma (NPC) in the United States are diagnosed with stage III-IV disease. Screening for NPC in endemic areas results in earlier detection and improved outcomes. We examined the cost-effectiveness of screening for NPC with plasma Epstein-Barr virus DNA among Asian American men in the United States. Study Design: We used a Markov cohort model to estimate discounted life-years, quality-adjusted life-years (QALYs), costs, and incremental cost-effectiveness ratios for screening as compared with usual care without screening. Setting: The base case analysis considered onetime screening for 50-year-old Asian American men. Subjects and Methods: Confirmatory testing was magnetic resonance imaging and nasopharyngoscopy. Cancer-specific outcomes, health utility values, and costs were determined from cancer registries and the published literature. Results: For Asian American men, usual care without screening resulted in the detection of NPC at stages I, II, III-IVB, and IVC among 6%, 29%, 54%, and 11% of those with cancer, respectively, whereas screening resulted in earlier detection with a stage distribution of 43%, 24%, 32%, and 1%. This corresponded to an additional 0.00055 QALYs gained at a cost of $63 per person: an incremental cost of $113, 341 per QALY gained. In probabilistic sensitivity analysis, screening Asian American men was cost-effective at $100, 000 per QALY gained in 35% of samples. Conclusion: Although screening for NPC with plasma Epstein-Barr virus DNA for 50-year-old Asian American men may result in earlier detection, in this study it was unlikely to be cost-effective. Screening may be reasonable for certain subpopulations at higher risk for NPC, but clinical studies are necessary before implementation.